CALCULATION OF RECEIVING CAPACITY OF POLLUTANTS IN THI NAI LAGOON (BINH DINH PROVINCE) - Trang, Cao Thi Thu; Vinh, Vu Duy (Vietnam Journal of Marine Science and Technology, 2016)
Based on the surveys at Thi Nai lagoon in rainy season (October, 2013) and dry season (May, 2014) and the documents on natural conditions, socio-economic status of Thi Nai lagoon, receiving capacity of pollutants in the lagoon was calculated on the basis of environmental standards, using Delft3D model. Calculation results showed that at present Thi Nai lagoon no longer has capacity to receive ammonium and nitrate. Until 2025, besides two parameters, Thi Nai lagoon will no longer have capacity to receive phosphate. In addition, the receiving capacity of the lagoon will be reduced for most of parameters while receiving capacity of lagoon for BOD5 and TSS will increase. Regarding heavy metals, receiving capacity of lagoon will be reduced, especially for Zn (12.18%).